Droplet-Enhanced Asymmetric Catalysis: Squaramide-Derived Pseudopeptide for Enantioselective Addition Reactions - Qipeng Chen; Donghua He; Yongjin Zhang; Chenxi Qiao; Jun Liu; Guohua Liu (Journal of the American Chemical Society, 2026)
Abstract Droplets formed through phase separation represent an emerging strategy to enhance enzyme-mimetic catalysis, demonstrating significant potential in catalytic science. However, due to the lack of systematic methodologies for precise engineering of chiral microenvironments within droplets, their application to asymmetric catalysis remains largely unexplored. To address this challenge, we integrate l-phenylalanine into an L-tert-leucine-derived squaramide to design the squaramide-derived pseudopeptide droplets. This catalytic system demonstrates remarkably enhanced catalytic performance in the enantioselective conjugate addition of α-nitrosulfone to acrylates and enones, as well as Michael addition of acetylacetone to β-nitroalkenes. Mechanistic investigations reveal that the increased local substrate concentration significantly enhances reactivity, while the engineered favorable chiral microenvironment boosts enantioselectivity. This study establishes a methodological framework for elucidating differentiated catalytic behaviors within the droplets, thereby advancing the design and application of droplet-based asymmetric catalytic systems.